2017
DOI: 10.1177/0272989x17715628
|View full text |Cite
|
Sign up to set email alerts
|

Who Decides: Me or We? Family Involvement in Medical Decision Making in Eastern and Western Countries

Abstract: These results suggest that it is important for health providers to avoid East-West cultural stereotypes. There are meaningful numbers of patients in all 7 countries who want to be individually involved and those individuals tend to prefer lower FI. On the other hand, more interdependent patients are likely to want families involved in many of the countries studied. Thus, individual differences within culture appear to be important in predicting whether a patient desires FI. For this reason, avoiding culture-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
65
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 85 publications
1
65
1
Order By: Relevance
“…We acknowledge that family and significant others can play a significant role in the process of decision making in some patients from non-Western cultural backgrounds. 57 However, one recent study 58 has suggested this may be less homogenous within cultures than previously thought. Another limitation is that we only included studies that were published in English and were identified from major databases in medical research.…”
Section: Discussionmentioning
confidence: 95%
“…We acknowledge that family and significant others can play a significant role in the process of decision making in some patients from non-Western cultural backgrounds. 57 However, one recent study 58 has suggested this may be less homogenous within cultures than previously thought. Another limitation is that we only included studies that were published in English and were identified from major databases in medical research.…”
Section: Discussionmentioning
confidence: 95%
“…5 Interestingly, this study included samples from many Eastern countries, including China, Thailand, South Korea, Malaysia and India; this finding also held in those countries, as well as in the USA and Australia. 5 Another study found that poor South Korean patients preferred autonomous TDM for end-of-life decisions, as they were often concerned that younger relatives might more heavily weigh financial concerns versus the patient's own preferences. 6 Researchers in the Asian Pacific region have therefore concluded that there are meaningful segments of patients across very different cultures who prefer little or no family involvement in TDM and higher levels of shared and autonomous TDM.…”
mentioning
confidence: 77%
“…2,3 Indeed, it has been observed that the majority of cancer patients prefer having a role in TDM along with their physicians; however, there is controversy regarding the appropriate level of involvement of patients' families. 4,5 In an online survey of 290 middle-aged urban residents, Alden et al found that individuals who preferred to be more involved in TDM-either as shared or autonomous TDM-tended to prefer less family involvement for a variety of illnesses ranging in severity, particularly if the family member in question was young. 5 Interestingly, this study included samples from many Eastern countries, including China, Thailand, South Korea, Malaysia and India; this finding also held in those countries, as well as in the USA and Australia.…”
mentioning
confidence: 99%
See 2 more Smart Citations